Theorising the structural dynamics of ethnic privilege in Aotearoa: Unpacking “this breeze at my back” - Moewaka Barnes, Helen; Borell, Belinda; Mccreanor, Tim (International Journal of Critical Indigenous Studies, 2014)
Colonial praxis has been imposed on the culture, epistemologies and praxis of indigenous Maori in Aotearoa, entrenching the settler cultural project that ensures the continuation of the colonial state, producing damaging disparities. This article theorises ways in which settler privilege works at multiple levels supporting settler interests, aspirations and sensibilities. In institutions, myriad mundane processes operate through commerce, law, media, education, health services, environment, religion and international relations constituting settler culture, values and norms. Among individuals, settler discursive/ideological frameworks are hegemonic, powerfully influencing interactions with Maori to produce outcomes that routinely suit settlers. In the internalised domain, there is a symbiotic sense of belonging, rightness, entitlement and confidence that the established social hierarchies will serve settler interests. This structure of privilege works together with overt and implicit acts of racism to reproduce a collective sense of superiority. It requires progressive de-mobilising together with anti-racism efforts to enable our society to move toward social justice.
Keywords: belonging; health; inequity; privilege; racism; wellbeing

Anti-Maori themes in New Zealand journalism--toward alternative practice - Moewaka Barnes, Angela; Borell, Belinda; Taiapa, Ken; Rankine, Jenny; Nairn, Ray; McCreanor, Tim (Pacific Journalism Review, 2012)
Gale Academic OneFile includes Anti-Maori themes in New Zealand journalism--toward alt by Angela Moewaka Barnes, Belinda Borell, . Click to explore.
Keywords: health; media; privilege; racism; representation; wellbeing